PENGETAHUAN SISWA SEKOLAH MAN 4 BALANGAN TENTANG TUMBUHAN OBAT DI KECAMATAN HALONG KABUPATEN BALANGAN PADA PELESTARIAN TUMBUHAN OBAT TRADISIONAL - Camsudin, Luhur Pribadi; Sholahuddin, Arif; Kissinger, Kissinger; Fauzana, Noor Arida (Universitas Lambung Mangkurat, 2024)
The Meratus Dayak people still believe that traditional medicine using medicinal plants can cure diseases and still often use it as needed. This traditional medicine has become extinct because the system of inheritance of knowledge is only through oral without any written records from generation to generation. This has led to a decrease in the number of individuals who have knowledge and skills in traditional medicine, especially in the younger generation who are less interested in learning traditional medicine. The purpose of this study was to analyze the knowledge of Madrasah Aliyah Negeri 4 Balangan students on medicinal plants, their use as daily or traditional customs and efforts to preserve traditional medicines in Halong Subdistrict, Balangan District. Students from class X IPA and X IPS at Madrasah Aliyah Negeri 4 Balangan have low knowledge about medicinal plants caused by several factors, including curriculum, teaching methods that are less interactive, the influence of parents who have limited knowledge, and modernization make modern medicines easier to obtain. Students have basic knowledge of medicinal plants, but limited to a few common types, there is a desire to expand their knowledge. The application of medicinal plants in everyday life is still low due to lack of practical knowledge and limited access.